A Clinical, Electrocardiographic and Echocardiographic Comparison of Patients with Single Vs Multivessel Disease Presenting with Acute Coronary Syndromes - Kumari Nuthalapat Rama; Kumar B Vijay (Journal of Hypertension and Cardiology, 2022)
Background Prevalence of coronary artery disease is between 7-13 percent in urban and 2-7 % in rural India1. The alarm in rise in the prevalence of coronary risk factors like diabetes, hypertension, dyslipidemia, smoking, central obesity and physical inactivity2. The correlation between these risk factors and the severity of coronary atherosclerosis, assessed by angiography which may be either single or multivessel is less consistent with studies reporting conflicting results 3,4. Therefore our study aims to understand the proper correlation between risk factors and severity of coronary artery disease in an Indian population Methods This study was conducted in the department of cardiology, NIMS hospital Hyderabad which receives patients from the urban as well as rural areas of Telangana. the patients admitted in the department of cardiology, NIMS hospital Hyderabad that presented with acute coronary syndromes and diagnosed to have coronary artery disease (single vessel/multivessel disease) on coronary angiography taken for study. Sample Size is 150 Results Among the 150 subjects, males were 111(74%) and females were 39(26%). Mean age of the study population is 55.2 ± 11.4. Among SVD group 73.65% were males &26.3% were females. Among MVD group 76.2% were males & 23.7% were females. Mean age for SVD was 53±14.4 years, while mean age foe MVD was 58.6±14.5 years. For ACS mean age of presentation for females is 60.7±11.4 and for males mean age of presentation is 55.1±12.6. MVD (57.2%) were more common among smokers than SVD. In <45 years age group SVD (69.2%) were more common than MVD (30.8%). In 45- 70 years age group and >70 years age group MVD were more common than SVD with 69.6% and 66.6% respectively, which is statistically significant. MVD (60%) were more common among hypertensives than SVD. Among non-hypertensives MVD (41.8%) was less common than SVD (58.2%) MVD was common among all age groups, which is statistically signicant. Among STEMI group SVD (58.3%) was more common than MVD (41.7%). Among NSTEMI group MVD (62%) was more common than SVD (38%).Correlation between groups was statistically significant. Among SVD study group, LVEF was commonly between 30-45% & very few with LVEF <30% MVD was associated with more severe LV dysfunction as compared to SVD in acute MI. The difference in ejection fraction between the two groups was statistically significant P value=0.0002. In hospital MACE Among SVD there was 1 MI (due to stent thrombosis) who had to TVR (primary PCI) & rest were asymptomatic and discharged in normal state MVD there were in hospital deaths (due to refractory cardiogenic shock) rest were asymptomatic and were discharged in normal state. This difference between the two groups was statistically insignificant. Conclusion Multivessel disease in ACS were seen more commonly among elderly as compared to young subjects where single vessel disease were more common. Females especially elderly more commonly have multivessel disease. Mean age for multivessel disease was higher than single vessel disease. Among <45 years age group, SVD was more prevalent among smokers, obese and physically active. Multi vessel disease is more prevalent among patients with risk factors like diabetes, hypertension, dyslipidemia and physically inactive. Subjects with family history of premature CAD presented early and correlated well with prevalence of SVD.NSTEMI presented more with multi vessel disease. In echocardiographic wall motion analysis, a depressed regional segment of infarcted area with remote hyperkinesis predicted SVD where as remote area hypokinesis predicts more multivessel disease. In hospital outcomes were seen among multi vessel disease as compared to single vessel disease although not statistically significant.
Keywords: ACS-Acute coronary syndrome